2018
DOI: 10.1200/jop.17.00029
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Continued Smoking and Smoking Cessation Among Patients With Cancer

Abstract: The perceptions of continued smoking after a cancer diagnosis among patients with cancer are strongly associated with smoking cessation. Counseling about the harms of continued smoking in patients with cancer, and in particular among those who have lower risk perceptions, should be considered when developing a smoking cessation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 43 publications
3
28
0
1
Order By: Relevance
“…We assessed patient perceptions on three survivorship outcomes through a brief screening tool used by our group previously. For each health behavior, patients were asked to rate the perceived impact of each behavior on three survivorship outcomes: quality of life, 5‐year overall survival, and fatigue after a cancer diagnosis using a 7‐point Likert scale (1 = “make much worse”, 4 = “no effect”, to 7 = “make much better”) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed patient perceptions on three survivorship outcomes through a brief screening tool used by our group previously. For each health behavior, patients were asked to rate the perceived impact of each behavior on three survivorship outcomes: quality of life, 5‐year overall survival, and fatigue after a cancer diagnosis using a 7‐point Likert scale (1 = “make much worse”, 4 = “no effect”, to 7 = “make much better”) …”
Section: Methodsmentioning
confidence: 99%
“…However, differences in both health behaviors and perceptions of these behaviors between immigrant and native‐born cancer survivors have not been explored. Previously, our group demonstrated that patient perceptions can be associated with health behavior changes after a cancer diagnosis …”
Section: Introductionmentioning
confidence: 99%
“…Apesar de o consumo de álcool não ter se demonstrado uma variável independentemente associada ao pior prognóstico, o consumo excessivo e contínuo de álcool após o diagnóstico de câncer pode levar à diminuição da taxa de remissão da doença e ao aumento na incidência de cânceres secundários no fígado e trato aerodigestivo superior com impacto indireto nas taxas de sobrevida 23 .…”
Section: Discussionunclassified
“…With the seemingly unparalleled rate of smoking among CCS , it is imperative to identify modifiable risk factors for smoking in this patient population. Despite theoretical and conceptual models that tie CA and risk (or benefit) perceptions to adjustment, motivation, and health behavior change after major life events like cancer diagnosis , and empirical support for these relationships in cancer survivors , these variables have not been explored in CCS.…”
Section: Discussionmentioning
confidence: 99%
“…The third major finding stands in contrast to those above, as many participants strongly endorsed smoking as a risk factor for poor clinical and quality of life outcomes after cancer diagnosis. Many CCS spoke at length about smoking's ill‐effects on risk for cancer recurrence and progression, poorer treatment experience and outcome, and worse quality of life, on par with some prior studies . This pattern of responding was not universal, though, as some participants were unsure about the risks of smoking after cervical cancer diagnosis and 1‐2 participants even indicated smoking has beneficial effects.…”
Section: Discussionmentioning
confidence: 99%